Herbal medicine as adjunctive therapy with antidepressants for post-stroke depression: a systematic review and network meta-analysis of randomized controlled trials - Zhang, Jian; Ming, Shuping; Chen, Xiaoming; Zhang, Teng; Qian, Hongyu; Peng, Shixiong; Ding, Yanbing (Frontiers in Pharmacology, 2023)
Herbal medicine can provide adjunctive therapy for adults with post-stroke depression. This study summarizes the latest evidence regarding the harms and benefits of herbal antidepressants. Our search included the Cochrane Library (OVID platform), Embase, PubMed, China National Knowledge Infrastructure (CNKI), Wan Fang Data Knowledge Service Platform, and China Scientific Journal Database (VIP) from inception until December 1, 2022. The systematic review focused on randomized controlled trials of herbal medicine in adults with post-stroke depression. We conducted a frequentist random-effect network meta-analysis and utilized the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework to categorize interventions, rate the certainty of the evidence, and present our findings. Out of the 1132 citations that were identified during the search, this study included 51 randomized clinical trials with a total of 4507 participants. The results showed that Shugan Jieyu capsule (SJC) plus selective serotonin reuptake inhibitors (SSRI), Jie-Yu Pills plus SSRI, and Wuling capsule plus SSRI were among the most effective interventions for response rate, with moderate certainty of evidence (RR: 1.45, 95%CI: 1.23 to 1.7; RR: 1.35, 95%CI: 1.09 to 1.68; RR: 1.32, 95%CI: 1.09 to 1.59). In terms of reducing symptoms of depression, Wuling plus Hypericum and Wuling capsule plus SSRI were found to be the most effective with moderate certainty of evidence (MD: -10.12, 95%CI: -17.25 to -2.99; MD: -3.81, 95%CI: -6.19 to -1.42) based on mean changes in Hamilton depression scale (HAMD) score after treatment completion. The network meta-analysis (NMA) showed that SJC may be a safer intervention than SSRI in terms of both total gastrointestinal and total nervous system events with moderate certainty of evidence (RR:0.34, 95%CI:0.18, 0.62 and RR: 0.11, 95%CI: 0.03, 0.35, respectively) .Overall, SJC plus SSRI, Jie-Yu Pills plus SSRI, and Wuling capsule plus were the most effective interventions for reducing symptoms of depression. Furthermore, the study showed no increased risk of gastrointestinal and nervous system events with low to very low certainty of evidence .